Las variaciones en los contratos de construcción: precisiones sobre su noción y causas - Vásquez Rebaza, Walter Humberto (2019)
One of the most important aspects of construction projects are their variations. These are situations that generate a series of negative consequences for those involved and constitute the breeding ground for claims and controversies, are inevitable in the construction industry. In the present article we will analyze two fundamental questions about variations: their conceptual delimitation and its causes. In general terms, we believe that a better understanding of the phenomenon will allow providing adequate and coherent solutions to the problem. The importance of this article derives from the vacuum at the legislative, doctrinal and jurisprudential levels in Peru. In effect, the regulation of the work contract contained in the Civil Code does not devote an organic treatment to variations. However, certain provisions of the mentioned normative body (as well as others included in sectoral disciplines) refer to the changes assigning them important legal effects.